James J. Hartley papers - Hartley, James J. (James Jasper), 1826-1864.
Chiefly letters between Hartley and members of his family during his Civil War service with the 122nd Ohio Infantry Regiment. Also includes printed matter and letters informing his wife, Melissa Jane Foreacre Hartley, of his death at the battle of Cold Harbor, Va.
In part, published in: The Civil War Letters of the Late 1st Lieut. James J. Hartley, 122nd Ohio Infantry Regiment / James J. Hartley; edited by Garber A. Davidson (Jefferson, N.C.: McFarland & Company, 1998)
U.S. army officer.
Collection material in English.
Keywords: Hartley, Melissa Jane Foreacre, -- 1831-1929.; United States. -- Army. -- Ohio Infantry Regiment, 122nd (1862-1865); Cold Harbor, Battle of, Va., 1864.; Ohio -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; Army officers